2019
DOI: 10.1177/1042258719890991
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion When Coping With Venture Obstacles: Loving-Kindness Meditation and Entrepreneurial Fear of Failure

Abstract: Entrepreneurial fear of failure is a ubiquitous yet aversive experience with critical implications for entrepreneurial action and well-being. To understand how entrepreneurs can effectively cope with fear-inducing obstacles, we hypothesize and experimentally test the extent to which self-compassion, cultivated through Loving-Kindness Meditation (LKM), counteracts entrepreneurs’ fear of failure when facing a threatening venture obstacle. Compared to an active control group, entrepreneurs exposed to a brief guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 122 publications
4
88
1
6
Order By: Relevance
“…The few interventions that have been published to-date focus on mindfulness and coaching. Mindfulness studies have employed loving-kindness meditation methods, delivered to a sample of entrepreneurs (Engel, Noordijk, et al, 2020) and through a Randomized Control Trial (Engel, Ramesh, et al, 2020), to mitigate their fear of failure, increase self-compassion, and heighten sustainable business practices. Coaching was employed by Schermuly et al (2020) with nineteen insolvent entrepreneurs.…”
Section: What We Know About Recovery In Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The few interventions that have been published to-date focus on mindfulness and coaching. Mindfulness studies have employed loving-kindness meditation methods, delivered to a sample of entrepreneurs (Engel, Noordijk, et al, 2020) and through a Randomized Control Trial (Engel, Ramesh, et al, 2020), to mitigate their fear of failure, increase self-compassion, and heighten sustainable business practices. Coaching was employed by Schermuly et al (2020) with nineteen insolvent entrepreneurs.…”
Section: What We Know About Recovery In Entrepreneurshipmentioning
confidence: 99%
“…For example, Brown et al (2014) examined the difference between lunchtime walking in nature, with lunchtime walking in industrial areas (as well as no walking at all). Less robust alternatives include using an active control, which requires participants to engage in an activity during the duration of the intervention time (e.g., watching TED talks; Engel, Noordijk, et al, 2020). Moreover, researchers can use a no-contact control, which means they engage in no activity, or a waitlist control, where participants have the expectation that they will participate in the experimental condition later (Boot et al, 2013).…”
Section: Collect Demographic Datamentioning
confidence: 99%
“…Research on resilience (Chadwick and Raver, 2018) and preventive coping (Reuter and Schwarzer, 2015), which concern the build-up of resources to deal with failure that may or may not occur in the future, may provide guidance here. One example of such a strategy is provided by Engel et al (2019), who found that engagement in loving kindness meditation mitigates levels of fear of failure when confronted with a hypothetical aversive business situation. Another example is defensive pessimism (Norem, 2008): a combined strategy of setting low expectations (being pessimistic) and taking pre-emptive preventative steps with regard to the things that might go wrong as one prepares for an upcoming situation or task.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Therefore, the hypothesis according to which fear of failure has a negative effect on entrepreneurial intentions was validated (H1). Engel et al [49] and Thomson et al [50] obtained similar results, showing that fear of failure affects entrepreneurs' well-being and their ability to act.…”
Section: Discussionmentioning
confidence: 75%
“…According to a study conducted by Henao-García et al [48], fear of failure either obstructs or motivates entrepreneurial behavior, according to the case, and influences the decision to start a new business. Engel et al [49] noted that fear of failure affects entrepreneurs' well-being and their ability to act. However, there is also the possibility that entrepreneurs' anxiety helps them achieve the required goals and standards, fear of failure being the result of anxiety and an accumulation of positive and negative emotions [50].…”
Section: Fear Of Failurementioning
confidence: 99%